2016
DOI: 10.1097/md.0000000000004064
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 23-valent pneumococcal polysaccharide vaccine on diabetic elderly

Abstract: Diabetes mellitus is associated with increased risk of pneumonia, and 23-valent pneumococcal polysaccharide vaccine (PPV23) is recommended for prevention of pneumonia. However, the effectiveness of PPV23 remains unclear in the older diabetic patients who usually have compromised immune function.We used data extracted from the Taiwanese National Health Insurance Research Database (NHIRD) from 2000 to 2009 to conduct a population-based retrospective cohort study, comparing the incidence of pneumococcal diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Likewise, the efficacy of 23-valent pneumococcal polysaccharide vaccine (PPV23) was found to be 84% in people with DM [ 14 ]. The 23-valent pneumococcal polysaccharide vaccination effectively prevented pneumococcal diseases and reduced utilization of medical services in elderly patients with diabetes aged 75 and more [ 15 ]. Furthermore, young and older adults with DM have been shown to mount optimal B-cell response to seasonal influenza vaccine [ 16 ].…”
mentioning
confidence: 99%
“…Likewise, the efficacy of 23-valent pneumococcal polysaccharide vaccine (PPV23) was found to be 84% in people with DM [ 14 ]. The 23-valent pneumococcal polysaccharide vaccination effectively prevented pneumococcal diseases and reduced utilization of medical services in elderly patients with diabetes aged 75 and more [ 15 ]. Furthermore, young and older adults with DM have been shown to mount optimal B-cell response to seasonal influenza vaccine [ 16 ].…”
mentioning
confidence: 99%
“…Pneumococcal vaccination efficacy in diabetes patients has also been shown by a retrospective cohort study conducted in approximately 67,000 elderly subjects that, via assessing, across a 9-year period, the Taiwanese National Health Insurance Research Database , reported a reduced risk by 14% of pneumococcal invasive disease onset in the group who received 23-valent pneumococcal vaccine (PPV23) compared with the group not exposed to PPV23 [ 27 ].…”
Section: Pneumococcal Infections In Subjects With Diabetesmentioning
confidence: 99%
“…Such a trial reported further benefits associated with Pneumococcal vaccination, since study subjects who received PPV23 experienced an improvement in – clinical and economic – outcomes such as hospitalization, respiratory failure, hospital stay and healthcare costs [ 27 ].…”
Section: Pneumococcal Infections In Subjects With Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Capsular PS is an important virulence determinant of the encapsulated bacteria and has been used as an antigen for preventive vaccine development [ 4 , 5 ]. However, the PS vaccines elicit weak T cell-independent immune responses without long-term immunological memories, particularly in children and the old [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%